PEMIKIRAN EKONOMI ISLAM DAN AKUNTANSI DI MASA DAULAH USTMANIYAH - Putri Ayu Ramadhani; Mukhtar Lutfi, Nasrullah Bin Sapa (CV. Adiba Aisha Amira, 2025)
This study aims to demonstrate the practices and accounting thought during the Ottoman Empire period. The accounting developed during that time is a concept of Islamic accounting that emphasizes the religious aspects of society while also improving the effectiveness of financial record-keeping. This research is a litera- ture review study using a historical approach from various sources and is classified as a bibliographic study. The findings of this research show that during the Otto- man period, Islamic accounting experienced significant development, and several theories emerged that combined both Islamic and conventional accounting prac- tices of that time.